2022
DOI: 10.3390/math10091395
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis of Fintech Risks in China: Based on Fuzzy Models

Abstract: Fintech has not changed the nature and risk attributes of financial business. Its openness, interoperability, and other characteristics trigger the concealment, infectivity, universality and sudden characteristics of financial risk more obviously, and the potential systemic risk more complexly. This paper adopts fuzzy set analysis to conduct a comprehensive review of Fintech risk. It is found that the technology risk, moral hazard and legal risk, with a weight of up to 80%, are the dominant factors affecting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…The application of this approach to internet financial risk warning and risk management research began as early as 2019 [ 15 ], gradually gaining momentum alongside technological development [ 11 , 19 , 25 ]. The primary focus of these studies lies in the selection of model methodologies [ 17 , 20 , 26 ] and the construction of risk systems [ 1 , 27 , 28 ]. However, to date, there has been no comprehensive review article or study systematically outlining the state of this emerging yet critical research field.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The application of this approach to internet financial risk warning and risk management research began as early as 2019 [ 15 ], gradually gaining momentum alongside technological development [ 11 , 19 , 25 ]. The primary focus of these studies lies in the selection of model methodologies [ 17 , 20 , 26 ] and the construction of risk systems [ 1 , 27 , 28 ]. However, to date, there has been no comprehensive review article or study systematically outlining the state of this emerging yet critical research field.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The performance of Dombi AOs when associated with Hamy [57] and Heronian [17] mean can also give us productive results in MADM problems. Further, such AOs-based theories can be utilized in Fintech risks [58], in the evaluation of noise reduction devices [59], and in the evaluation of green supply chains [59,60].…”
Section: Discussionmentioning
confidence: 99%
“…Just similar to insurance, moral hazard often is accompanied with finance. For instance, Fintech Risks in China and found that the technology risk, moral hazard and legal risk are the dominant factors affecting the Fintech risk (Tianlei Pi et al, 2022). Simultaneously, Xueer Chen and Chao Wang(2021) demonstrated that the application of Fin Tech in China's banking industry resulted in less information asymmetry.…”
Section: Moral Hazardmentioning
confidence: 99%